THE ROLE OF PROBIOTICS AND GUT MICROBIOTA MODULATION IN THE PATHOGENESIS AND MANAGEMENT OF ACNE VULGARIS: A SYSTEMATIC REVIEW - Jóźwicka, Agnieszka; Bąkowska , Ewa; Janikowski , Wojciech; Stępka, Aleksandra; Jaworowicz, Lena; Plichtowicz-Kordowska, Weronika; Lewandowska, Karina; Wieczorek, Maria (International Journal of Innovative Technologies in Social Science, 2026)
Background: Acne vulgaris is a multifactorial inflammatory skin condition. Recent evidence highlights the critical role of the gut-skin axis and gastrointestinal dysbiosis in its pathogenesis, suggesting that systemic inflammation originating in the gut may exacerbate cutaneous symptoms. Objective: This systematic review aims to evaluate the clinical efficacy, microbiological specificity, and safety profile of probiotic interventions in the management of acne vulgaris. Methods: A comprehensive literature search was conducted across PubMed and Google Scholar databases to identify relevant experimental and clinical studies investigating the relationship between the gut microbiome, probiotic supplementation, and acne development. Results: Current data demonstrate that both oral and topical probiotic interventions significantly reduce inflammatory and non-inflammatory acne lesion counts. Oral probiotics primarily modulate the gut-brain-skin axis, lowering systemic inflammation and regulating sebum excretion rates (SER). Topical applications directly restore the cutaneous barrier and competitively inhibit Cutibacterium acnes. Efficacy is highly strain-specific, with Lactobacillus and Bifidobacterium species showing the most significant benefits. Furthermore, probiotics serve as highly effective adjuvant therapies, synergistically improving clinical outcomes while mitigating the adverse effects of conventional treatments such as systemic antibiotics and isotretinoin. Conclusion: Microbiome-targeted therapies, specifically probiotics, represent a safe, well-tolerated, and promising adjunctive strategy in acne management. Further large-scale, randomized controlled trials are required to establish standardized, strain-specific therapeutic protocols.